Notes on the known species of Trichomyia Haliday of Mexico, with the establishment of a synonymy and the description of a new species (Diptera: Psychodidae) - Ibáñez-Bernal, Sergio (Zootaxa, 2004)
Only three species of Trichomyia Haliday have been recorded in Mexico. Trichomyia cirrata Coquillett, 1902, is recognized by its female characteristics, T. fairchildi Vargas and Díaz-Nájera, 1953, was described based only on the wing and must be considered as species inquirenda, and T. maldonadoi (Vargas, 1953), which was described based on one female specimen. Specimens of Trichomyia collected in the states of Campeche, Yucatan, and Oaxaca, Mexico, allowed this female to be associated with the male of T. brevitarsa (Rapp, 1945), thus providing a first report of this species in Mexico. Consequently, T. maldonadoi is proposed as a synonym of T. brevitarsa. Additionally, a new species of Trichomyia from the state of Veracruz, Mexico, is described and illustrated based on the male and female characteristics.